Diarrhea with deficiency kidney-yang syndrome caused by adenine combined with Folium senna was associated with gut mucosal microbiota - Zhu, Jiayuan; Li, Xiaoya; Deng, Na; Peng, Xinxin; Tan, Zhoujin (Frontiers in Microbiology, 2022)
ln order to study and analyze the characteristics of gut mucosal microbiota in diarrhea mice with deficiency kidney-yang syndrome. Ten male mice were randomly divided into the control group and the model group. Diarrhea mice model with deficiency kidney-yang syndrome was established by adenine combined with Folium sennae. The kidney structure was observed by hematoxylin eosin (HE) staining. Serum Na+-K+-ATP-ase and Ca2+-Mg2+-ATP-ase were detected by enzyme-linked immunosorbent assay (ELISA). Characteristics of gut mucosal microbiota were analyzed by third-generation high-throughput sequencing. Results showed that model mice have obvious structural damage of kidney. Serum Na+-K+-ATP-ase and Ca2+-Mg2+-ATP-ase levels had decreased trends in the model group. Diversity and community structure of gut mucosal microbiota improved in the model group. Dominant bacteria Candidatus Arthromitus, Muribaculum, Lactobacillus reuteri varied significantly at different taxonomic levels. Characteristic bacteria Bacteroides, Erysipelatoclostridium、Anaerotignum Akkermansia muciniphila、Clostridium cocleatum、Bacteroides vulgatus and Bacteroides sartorii were enriched in the model group. Correlation analysis described that Erysipelatoclostridium was positively correlated with Na+-K+-ATP-ase and Ca2+-Mg2+-ATP-ase, while Anaerotignum had the opposite. Together, adenine combined with Folium sennae damaged kidney structure, affected energy metabolism and caused disorders of gut mucosal microbiota in mice. Bacteroides, Erysipelatoclostridium and Anaerotignum had significant inhibition or promotion effects on energy metabolism. Besides, Akkermansia muciniphila、Clostridium cocleatum、Bacteroides vulgatus and Bacteroides sartorii might be the characteristic species of gut mucosal microbiota causing diarrhea with deficiency kidney-yang syndrome.